Economic Policy and Equity. (International Monetary Fund, 1999)
This book brings together the views not only of policymakers and academics but also of religious leaders and labor leaders from around the world- including the 1998 Nobel Laureate in Economics, Amartya Sen - who participated in an IMF conference on this topic. Contributors discuss the causes of growing inequality and the complex question of how to use policy to make economic systems more equitable under five headings: perspectives on economic policy and equity, globalization and equitable growth, country experiences in equity-oriented policymaking, design and implementation of policy, and a roundtable discussion on lessons for countries and the IMF. Edited by Vito Tanzi, director of the Fiscal Affairs Department of the IMF; Ke-young Chu, a senior advisor; and Sanjeev Gupta, a division chief in the department.